Study on Energy Input, Output and Energy Use Efficiency of Major Jute Based Cropping Pattern (Bangladesh Journal of Scientific and Industrial Research, 2007)
An investigation was undertaken in Jute Research Regional Station, BJRI, Kishoreganj during the period of 2000 - 2001 to 2002 - 2003 to evaluate the energy input, energy output and output-input ratio of some selected jute based cropping pattern. the result showed that the highest energy input (42,928 MJ ha-1) was noted for Jute (oli.)- T. aman rice-Potato, which was closely followed by Jute (cap.)-T. aman rice-Potato cropping pattern (39.856 MJ ha-1). The lowest energy input (19,947 MJ ha-1) was found for Jute (cap.)-T. aman rice-Fallow pattern. The highest energy output from main product was recorded in Jute- T. aman rice-Potato cropping pattern while the lowest from Jute-Fallow-Wheat pattern. However, the highest total energy output was obtained from Jute-T. aman rice-Wheat (4,01,332-403851 MJ ha-1) which was followed by Jute-T. aman rice-Potato (3,66,729-3,73,949 MJ ha-1) and Jute-T. aman rice-Lentil (2,88,906-3,33,416 MJ ha-1), although the energy output from main product of potato containing cropping pattern was the highest. The energy output from by-product was more compared to main product for all the cropping patterns. Between two jute based cropping patterns, olitorius jute containing pattern required higher energy input than that of capsular is but energy output was higher in capsularis jute containing pattern. Output-input ratio of cropping pattern was maximum (14.5) in 2-crop pattern where rabi crops were absent. It indicated that rabi crops had lower energy output compared to other kharif crops. Bangladesh J. Sci. Ind. Res. 42(2), 195-202, 2007